CODE-SWITCHING IN INTERCULTURAL COMMUNICATION AMONG FORMER IISMA STUDENTS AT UC CHILE ( A SOCIOLINGUISTIC ANALYSIS) - Rafael Dwi Putra Momongan; Jultje Aneke Rattu; F. Ari Anggriani Sebayang (Universitas Sam Ratulangi, 2026)
This study examines the use of Indonesian–English–Spanish code-switching among former Indonesian International Student Mobility Awards (IISMA) students at the Pontificia Universidad Católica de Chile (UC Chile). It aims to identify the types of code-switching employed, analyze their communicative functions, and explain how such practices support intercultural communication and adaptation in a Spanish-speaking academic environment. This research adopts a qualitative approach within the framework of interactional sociolinguistics and intercultural communicative competence. The findings reveal that intra-sentential switching is the most dominant type, indicating a high level of multilingual competence among the participants. Code-switching serves several key functions, including clarification, solidarity and identity marking, and emphasis. Among these, clarification is the most frequent, reflecting the need to maintain mutual understanding in a multilingual environment. Furthermore, code-switching supports intercultural communication by facilitating interactional flexibility, enhancing cultural awareness, and enabling speakers to adapt to different communicative contexts. In conclusion, code-switching is not merely a linguistic phenomenon but a strategic communicative resource that plays a significant role in intercultural adaptation. This study contributes to sociolinguistic and intercultural communication research by highlighting the importance of trilingual code-switching in non-English-speaking academic settings.